Heritage interpretation: collective reconstruction of Sompur Mahavihara, Bangladesh - Rahman, Hafizur; Rashid, Md. Mizanur (IEEE, 2010)
The increasing development of Virtual Reality (VR) technologies, interfaces, interaction techniques and devices has greatly improves the efficacy and usability of VR, which has helped institutions of informal education, such as museums, media research and cultural centres to embrace advanced virtual technologies and support their transaction from the research laboratory to the public realm. The 8th century Buddhist Monastery of Sompur Mahaviahara at Paharpur drew deep attention by the architectural historians of the South Asia from the very discovery of the ruins for its unique architectural features and strategic spatio-temporal location. During the first phase of study, we have developed a preliminary reconstructed 3D model of Sompur Mahaviahara – as ‘professional interpretation’. The second phase is attempted to investigate about ‘public interpretation’. We propose a novel approach of heritage interpretation for general public opposing the traditional interpretation method. With an interactive system, supported by active online participants to collaboration and collectively generate a knowledge base of cultural memories. We hope through this participatory approach of reconstruction/interpretation will provide an understanding of public view about this monument and at the same time will allow differentiating the deviation of the professional and public reconstruction. As a methodology ‘heritage interpretation’ is first conceptualized; followed by elaboration of professional interpretation. Finally a conceptual interpretation has been proposed for public interpretation.